Effect of polymorphism in the 5’ promoter region of the TG gene on the milk production traits of Polish Holstein-Friesian cattle - Ewa Czerniawska-Piątkowska (Polish Society of Animal Production, 2020)
The aim of the study was to determine the relationship between the occurrence of three different point mutations (257C>T, 335A>G and 422 C>T) in the promoter region of the gene encoding thyroglobulin (causing polymorphism) and the milk production traits of cattle. The research was conducted on a herd of Polish Holstein-Friesian cows. Genotypes were determined by PCR and its ACRS modification. The frequency of more common alleles for the point mutations was determined: C ‒ 0.830 (257C>T), A ‒ 0.765 (335A>G), and C ‒ 0.635 (422C>T). The statistical analysis showed that all three point mutations in the promoter region of the TG gene significantly (P ≤ 0.05; P ≤ 0.01) affect the analysed milk production traits, i.e. daily milk yield, content of milk fat and protein, and somatic cell count.